(untitled) (Environment & Health, 2022)
Objective: We substantiated a hygienic standard for air exchange multiplicity in the doctors’medical premises at the ambulances built into residential houses to preserve and strengthen their health. Materials and methods: The analytical method was applied in the work (regulatory framework of sanitary and town-planning legislation, development of the hygienic standard by calculation method). The air exchange calculation for the working places of family doctors of the built-in ambulances was carried out in accordance with the NBS B.2.5-67:2013 Heating, Ventilation and Air Conditioning. Results and discussion: The calculation of air exchange rate for the doctors’ working places of the healh care facilities built into the residential houses was carried out in accordance with the NBS B.2.5-67:2013 Heating, Ventilation and Air Conditioning (Annex X (mandatory) Minimum Outdoor Air Consumption) and corresponding formulas. To calculate the air exchange in the doctors’premises, the category of the works of the doctors of the ambulance medical practice, which refers to light physical (office) work by the category I; the number of nurses at work at the same time and the potential number of visitors (2 persons - doctor and patient; 3 persons - doctor, nurse and patient and / or doctor, patient and accompanying person; 4 persons - doctor, nurse, patient and accompanying patient person); the minimum air consumption per 1 person - 60 m3 / hour; the regulatory size of the area of the medical premises (12 m2, 18 m2) and different types of housing estate with 2.5 m and 3 m premise high were taken into account. Conclusions: To replace the current standard K = 1 (NBS B.2.2-10-2001 Health Care Facilities), the standards of optimal air exchange multiplicity K = 6.44 and K = 8.40 in doctors’ medical facilities with different sizes and the number of people staying simultaneously were substantiated on the basis of the conducted hygienic study of the conditions of the placement of modern health care facilities of ambulance type built into residential houses. In order to ensure strengthening and preservation of the health of medical staff and patients and to create the proper sanitary and anti-epidemic working conditions for staff, the health care facilities, built into residential houses, need the mechanical plenum-exhaust ventilation according to the new reasonable standards of air exchange multiplicity for medical premises.